Investigative Journalism in the Era of a Crisis of Democracy: The Example of Hungary - Wojciech Adamczyk (Barometr Regionalny, 2023)
The subject of the article is the functioning and role of investigative journalism in Hungary in the conditions of the tendency to move from liberal democracy towards autocracy, which has been observed for over two decades. This leads to the restriction of civil liberties in various areas of social life, including the sphere of activity of the independent media, which are obviously perceived by the rulers as an obstacle in appropriating the state and achieving goals contrary to the interests of citizens. Under the rule of Viktor Orbán, the leader of the Fidesz party, since 2010 a plan to monopolize the circulation of information and subordinate the media and advertising market to the ruling party has been consistently implemented. Internet sites of investigative journalism are the only enclaves of independent journalism, identified with the concept of the “fourth power.” Three such portals were analyzed, pointing to their economic basis, the methods of conducting and the subject of their investigations, and the effectiveness in publicizing irregularities in the conduct of the rulers and businessmen associated with power.